Within-Network Connectivity in the Salience Network After Attention Bias Modification Training in Residual Depression: Report From a Preregistered Clinical Trial - Hilland, Eva; Landrø, Nils I.; Harmer, Catherine J.; Maglanoc, Luigi A.; Jonassen, Rune (Frontiers in Human Neuroscience, 2018)
Alterations in resting state networks (RSN) are associated with emotional- and attentional control difficulties in depressed individuals. Attentional Bias Modification (ABM) training may lead to more adaptive emotional processing in depression, but little is known about the neural underpinnings associated with ABM. In the current study a sample of 134 previously depressed individuals were randomized into 14 days of computerized ABM- or a closely matched placebo training regime followed by a resting state MRI scan. Using independent component analysis (ICA) we examined within-network connectivity in three major RSN’s, the default mode network (DMN), the salience network (SN) and the central executive network (CEN) after two weeks of ABM training. We found a significant difference between the training groups within the SN, but no difference within the DMN or CEN. Moreover, a significant symptom improvement was observed in the ABM group after training.